Pengaplikasian Mediasi dalam Perceraian di Era Pandemi Covid-19 pada Pengadilan Agama Pasangkayu (Tinjauan Yuridis-Normatif) - Fahmi, Nazil (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
Mediation is an alternative part of resolving cases that prioritizes the principles of justice and the good faith of the litigants who have experienced changes in their implementation in the world of judicial institutions during the Covid-19 pandemic, especially in religious courts. So, this study intends to describe the problem in a research question that has been formulated, namely how to apply divorce’s mediation in the era of the Covid-19 pandemic at the Pasangkayu Religious Court which is reviewed from a juridical-normative perspective. Then, the selection of the research method used is a type of qualitative research and data collection by means of field research. Meanwhile, juridical-normative is a research approach. Observing the research problems that have been formulated, the results of the study explain that mediation is applied in two closed stages, namely the pre-mediation stage and the mediation implementation stage and adjusts to the current situation. The purpose of mediation that adapts to circumstances is that mediation in divorce at the Pasangkayu Religious Court has changed according to the conditions that occurred in the era of the Covid-19 pandemic which caused the mediation model, especially in carrying out mediation using two ways, namely carrying out virtual mediation and maximizing caucuses (separate meetings). The two models of mediation application have actually been regulated in a juridical-normative manner, in which their application has a legal umbrella in the Supreme Court Regulations (PERMA), Supreme Court Circular Letters (SEMA) and policies from the Religious Courts Agency (BADILAG).